2012
DOI: 10.1007/s12028-012-9703-3
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Hemicraniectomy in Malignant Middle Cerebral Artery Infarct: A Randomized Controlled Trial Enrolling Patients up to 80 Years Old

Abstract: For patients up to 80 years who suffered mMCAI, DHC within 48 h of stroke onset not only is a life-saving treatment, but also increases the possibility of surviving without severe disability (mRS = 5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
133
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(140 citation statements)
references
References 25 publications
3
133
1
3
Order By: Relevance
“…In the present study, three patients over 60 years of age were included. A Chinese study evaluated the effectiveness of DC in patients over 80 years of age, concluding that DC, even in patients in this age group, may increase the survival rate without severe compromise of functionality 18 . In a recent American study, involving more than 1,600 patients, the authors reported the results according to age as uni-and multivariate analysis, not taking into account this variable as a significant predictor of clinical outcome 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, three patients over 60 years of age were included. A Chinese study evaluated the effectiveness of DC in patients over 80 years of age, concluding that DC, even in patients in this age group, may increase the survival rate without severe compromise of functionality 18 . In a recent American study, involving more than 1,600 patients, the authors reported the results according to age as uni-and multivariate analysis, not taking into account this variable as a significant predictor of clinical outcome 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Six RCTs comprising 289 patients met our inclusion criteria: 4 completed trials of early DC, the published preliminary results from a trial of early DC, and a subgroup analysis comprised of patients randomized within 48 hours from Hemicraniectomy After Middle Cerebral Artery Infarction With Life-threatening Edema Trial (HAMLET), a DC trial which enrolled patients up to 96 hours from onset (table). 5,10,11,[23][24][25] One study was excluded, Hemicraniectomy and Durotomy Upon Deterioration From Infarction-Related Swelling Trial (HeADDFIRST), which enrolled patients up to 96 hours from onset and, notably, intentionally delayed DC until patients had severe clinical or radiographic deterioration. 26 Inclusion criteria for the individual trials were similar, with exception of the prespecified age ranges (table).…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…The 4 completed RCTs of early DC, Jüttler et al, 25 Vahedi et al, 24 Zhao et al, 11 and Jüttler et al, 10 received a low risk of bias rating. Slezins et al 23 is a brief preliminary report that does not comprehensively detail study methodology.…”
Section: Risk Of Bias For Independent Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current issue of Neurocritical Care, Zhao and colleagues report the results of a Chinese randomised controlled study [9] which investigated the effect of early decompressive hemicraniectomy after large mMCAI in patients aged 18-80 years. Forty-seven patients were included in the trial and 24 of them were randomized to early DHC.…”
mentioning
confidence: 99%